Prohibiting Political Party Membership as a Condition for Receiving Political Service Retirement Benefits under Ethiopian Law: A Comparison with Kenya and Tanzania - Tesfay, Leake Mekonen (Journal of African law, 2024)
This article questions the justification for restricting political party membership as a condition for receiving political service retirement benefits in Ethiopia (a restriction first imposed through the Administration of the President of the Federal Democratic Republic of Ethiopia Proclamation and endorsed in the Rights and Benefits of Outgoing Heads of State and Government, Senior Government Officials, Members of Parliament and Judges Proclamation). After reviewing relevant law, literature and comparative experience from Kenya and Tanzania, the article argues that prohibiting political party membership without a pressing need for non-partisan service is an unjust restriction on the right to freedom of political party membership. Benefits for retiring high-ranking government officials are part of the right to social security and should not be disallowed based on political party membership.